The verb in textbooks for learning Italian as a second language - Troncarelli, Donatella (Kwartalnik Neofilologiczny, 2026)
The verb is one of the most complex grammatical categories for learners of Italian as a second language, given the wide variety of forms and the high density of grammatical information conveyed by verbal morphology. This study investigates how instructional materials address this complexity by examining the presentation and treatment of verbs in Italian L2 textbooks.